Islamic Bussiness Concept In Facing Moral Hazard Of Mudharabah Financing In Indonesia Islamic Banking (Perspective: Asymetric Information Theory) - Sholihah, Ummu; Fatwa, Nur (UI Scholars Hub, 2021)
In the contract of financing much-needed information asymmetry between the owners of capital (shahibul mall) and the manager of the capital (mudharib) in order to achieve common interests. One of the indicators that lead to moral hazard is due to asymmetric information or dissimilarity of information provided, and influential in the contract of financing. In a Mudharabah financing contract, between shahibul mall and mudharib provide information asymmetry in favor of the creation of a common interest. This study is a literature with an approach that combines the philosophical and phenomenological approach to look deeply about the material object of philosophy as well as the value, the principle of principles, objectives and economic policy, as well as concepts especially the system of financing which is born of the concept of Islamic business. While the phenomenological approach is used in view of economic development, well illustrated in society through statistical data, as well as those contained in a work of literature. The data source literature in particular are books, journals and articles standard, both with regard to the business concept of Islam which were analyzed using content analysis techniques. As the conclusion, in the mudharabah financing contract, asymmetric information is needed between the owner of the capital (shahibul mal) and the capital manager (mudharib) in order to achieve common interests. And one of the indicators that causes moral hazard is the result of asymmetric information or inequality in the information provided, which affects the mudharabah financing contract.